The economics of contemporary Latin America - Armendariz de Aghion, Beatriz, 19..-; Larrain B., Felipe (MIT Press., 2017)
Analysis of Latin America's economy focusing on development, covering the colonial roots of inequality, boom and bust cycles, labor markets, and fiscal and monetary policy. Latin America is richly endowed with natural resources, fertile land, and vibrant cultures. Yet the region remains much poorer than its neighbors to the north. Most Latin American countries have not achieved standards of living and stable institutions comparable to those found in developed countries, have experienced repeated boom-bust cycles, and remain heavily reliant on primary commodities. This book studies the historical roots of Latin America's contemporary economic and social development, focusing on poverty and income inequality dating back to colonial times. It addresses today's legacies of the market-friendly reforms that took hold in the 1980s and 1990s by examining successful stabilizations and homemade monetary and fiscal institutional reforms. It offers a detailed analysis of trade and financial liberalization, twenty first century-growth, and the decline in poverty and income inequality. Finally, the book offers an overall analysis of inclusive growth policies for development including gender issues and the informal sector and the challenges that lie ahead for the region, with special attention to pressing demands by the vibrant and vocal middle class, youth unemployment, and indigenous populations.